2023
DOI: 10.3390/ani13050862
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of Central and Peripheral Nervous System Lymphoma in Dogs and Cats: A Study of 92 Cases and Review of the Literature

Abstract: The literature about nervous system lymphoma (NSL) in dogs and cats is fragmentary, based on a few case series and case reports with heterogeneous results. The aim of our study was to retrospectively analyze 45 cases of canine and 47 cases of feline NSL and compare our results with previously reported data, also providing an extensive literature review. Breed, age, gender, clinical signs, type, and neurolocalization were recorded for each case. The pathological patterns and phenotype were assessed by histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…5 Infiltration of these compartments as well as the pituitary gland and choroid plexus was more com-mon with B-cell than T-cell lymphoma in a study of 37 dogs. 2,5 The same authors reported that in the studied dogs, 81% had involvement of more than one compartment. 5 Large granular lymphocytes are a subset of lymphocytes featuring intracytoplasmic azurophilic granules and are normally present in small quantities in peripheral blood.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…5 Infiltration of these compartments as well as the pituitary gland and choroid plexus was more com-mon with B-cell than T-cell lymphoma in a study of 37 dogs. 2,5 The same authors reported that in the studied dogs, 81% had involvement of more than one compartment. 5 Large granular lymphocytes are a subset of lymphocytes featuring intracytoplasmic azurophilic granules and are normally present in small quantities in peripheral blood.…”
Section: Discussionmentioning
confidence: 84%
“…2 The largest study to date includes data of CNS and PNS lymphoma from 92 dogs and cats. 2 In a recent study of 45 cases of central and PNS lymphoma in dogs, the majority of the lesions were located intracranially (49%), followed by spinal canal (31%) and PNS (20%). 2 In that study, ocular involvement was not mentioned in any of the included cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations